A blended learning environment based on the principles of deliberate practice for the acquisition of interpreting skills. Issue 1 (2nd January 2016) - Motta, Manuela
ABSTRACT: Students who enrol in a conference interpreting programme start out as novices and are expected to become experts by the end of a post-graduate programme. From then on, they are expected to produce high-quality performances for their entire professional career, without benefitting from virtually any structured or formal appreciation of their work, if they work as freelance intepreters, with the exception of occasional feedback from clients or peers; hence, the need for students to become adaptive experts, i.e. autonomous learners who can think and act as professionals. We believe that real-life problem-based deliberate practice in situated learning environments helps learners reach this objective. The blended learning environment adopted at the Interpreting Department, University of Geneva, promotes a collaborative approach to learning by means of activities anchored in real context and helps learners become autonomous, meta-cognitive and self-regulated under the guidance of the scaffolding and modelling skills of teaching assistants. This article describes how this pedagogical approach to training is implemented and in what way it contributes to training students to become adaptive experts. Results of the study that was carried out to evaluate the learning environment, and more specifically its blended tutoring programme, will be used to substantiate this theory-driven approach.